Serie 2, no. 4, EN: September de 2017 - Millenium Millenium (Instituto Politécnico de Viseu, 2017)
Millenium journal reaches the end of the first year of series 2, with this number 4. September 2017 marks the effort of a new editorial policy that is translated into the publication of four numbers with articles simultaneously in Portuguese and English, whose scientific quality was rigorously attested by blind peer review and whose authors are external to the IPV. Two more issues were also published as Special Edition. This issue maintains the objective of a multidisciplinary and transdisciplinary journal of diffusion of scientific and technological knowledge based on the premise that the different scientific areas and research increasingly cross and complete each other. In the Engineering, Technology, Management and Tourism section, the article "Shopping intention prediction using decision trees" examines the purchasing decision making process and how it can be very challenging for the client. For that, it was created a two categories model to prevent the purchase intent and to segment customers, depending on the intent to buy it or not. Finally, in "Internal vs. external service quality: reflections of employees and customers in the mirror" it is investigated the relation of the perception of the quality of the internal service by the members of the faculty, with the perceptions of quality of the students and it was concluded that these were positively related. The section "Education and Social Development" begins with the article "Student's learning processes for sustainable knowledge" which aims to identify how students are using the design of a curricular unit to create knowledge about Sustainable Business Development, intending to contribute for the knowledge about the learning processes at university level. It concludes that there is a need to introduce individual and collective learning processes and that the facilitation of theseprocesses should be a task for educational agents. The second article in this section "Almadrava: Men and sea. Social relationship in a short-term community", using documentary analysis and interviews, aims to be a wakeup call for the preservation of the collective memory of arts and the ways of life of a fishing village in the south of Portugal. Comparing internal and external quality of service levels will help managers set priorities for allocating resources to improve quality. The Health and Life Sciences section integrates four articles, thefirst being "Ontology elements identified in different nursing classification systems", which aims to facilitate the development of ontologies for nursing practice based on nursing terminologies, contributing, this way, to the development of health policies and the use of ontologies in information systems. The study "Perception of quality of life of people with drug addiction", which assesses the perception of Quality of Life (QL) of people related to drug addiction, and which aims to identify groups with greater vulnerability, with a view to planning interventions. The third article "Deaf people's satisfaction with the health care system quality" documents the level of satisfaction of the deaf person concerning the quality of the actions and services offered in the Brazilian public health units. Finally, the article "Music therapy as an autonomous intervention of nurses for pain control in ICU: integrative review" concludes, in its integrative review, that music therapy is an autonomous nursing intervention that can be used as nonpharmacological intervention in the control of pain, in patients with specific needs inherent to an ICU.  This number ends with the section Agrarian, Food and Veterinary Sciences, with the article "Education as a tool to reduce the water footprint of young people". This article analyzes the role of youth education and its role in sustainable water management and concludes that young people are consuming too much water, and should review their habits related to food, clothing, and the duration of daily showers.